IMPLEMENTASI MANDAT MISI:: PROSES MENJADIKAN MURID BERDASARKAN MATIUS 28:18-20 - Sumampouw, Alexander (STT-RAI Batam, 2024)
Matthew 28:18-20, is the primary source for understanding the mandate and mission of Jesus Christ to His disciples. This Great Commission, which includes the granting of authority, the ongoing mandate, and the promise of inclusion by Jesus, forms the basis for discipleship in the Christian Church. This study identifies several key objectives of discipleship, including solidifying the foundations of Christian belief, creating a Christian image in the life of the disciple, and learning and applying God's Word. It also includes a discussion of the characteristics of discipleship, which emphasizes the importance of personal growth, Bible knowledge, and ministry direction in disciple formation. The Gospel of Matthew, as one of the synoptic Gospels, is considered unique in its systematic arrangement, which reflects the purpose and authority given to Jesus' disciples. This study aims to provide an explanation that the purpose of discipleship covers all aspects of a believer's life, with a focus on personal growth, theological knowledge, and service inspired by the Word of God. The concept of the Great Commission as a foundation in the discipleship process, emphasizing the importance of understanding and applying the mandate as a mission process to make quality disciples given by Jesus Christ to His disciples. This article provides a framework for understanding how the Great Commission can be implemented in discipleship practice, taking into account aspects such as personal growth, biblical knowledge, and ministry direction. This research utilizes a qualitative method with a literature review approach. The result of this study is to provide an in-depth insight into how Mission as a process to make disciples in implementing the Great Commission based on Matthew 28:18-20 becomes the basis of ministry for the Church in carrying out mission, by emphasizing the importance of understanding and implementing the mandate and mission given by Jesus to His disciples.